Association of airway inflammation and smoking status with IL-33 level in sputum of patients with asthma or COPD - Abdo, Mustafa; Pedersen, Frauke; Kirsten, Anne-Marie; Trinkmann, Frederik; Groth, Espen E.; Bahmer, Thomas; Watz, Henrik; Rabe, Klaus F. (The European respiratory journal, 2024)
Asthma and COPD are heterogeneous inflammatory airway conditions. Interleukin (IL)-33 is an epithelial pleiotropic cytokine that regulates type 1 and type 2 immune responses [1]. Clinical trials have shown promising efficacy of monoclonal antibodies targeting IL-33 and its ST2 receptor in asthma and COPD [2-4]. So far, little is known about the characterisation of airway inflammation associated with increased IL-33 levels in patients with asthma or COPD. Moreover, previous studies have reported a potential impact of smoking status on IL-33 protein levels [5]. Therefore, we investigated the association of smoking status and airway inflammatory phenotypes with IL-33 levels in patients with asthma or COPD. Such clinical characterisation could provide new insights for selecting patients who might benefit from anti-IL-33 therapy.
Gesehen am 04.08.2025